Initial application of modelling techniques in livestock production systems under semi-arid conditions in Africa - Anderson, F.M.; Trail, J.C.M. (International Livestock Centre for Africa, 1978)
Comparison of broad data base & scarce data base situations, where modelling can play a positive role in research towards livestock production systems in Africa, w. specific examples from Botswana and Mali.